THE SOCIAL IMPACT OF EMERGING TECHNOLOGIES: A COMPARATIVE STUDY OF AI ADOPTION ACROSS CULTURES - Aruna, Kookutla; Kumari, Y Saritha; Parla, Suresh; Naveen, Sudhamsetti; Galavilli, Subha; Raj, Arpana (ShodhKosh: Journal of Visual and Performing Arts, 2024)
AI has brought changes across different Cultural, Economic and Social frontiers across the world. The sample objectives of this study include a comparison of the social effects of AI in different cultures with emphasis on the manners through which the adoption of this innovation relates to the social organization; work; learning; and ethical practices in culturally distinct environments. AI has been used intensively in organizations to increase efficiency and creativity but acceptance of AI in various societies depends on cultural beliefs, attitudes, and technological adoption. This comparative research aims to critically explore culture and government policies, educational systems, and ethical issues on the formation of social effects of AI. By addressing AI adoption within numerous cultural perspectives including western, east and the global south paradigms, the study reveals the ethical issues, workforce evolution and sociopolitical changes that have been informed by the growth of Artificial Intelligence. Moreover, this research explores how different cultural stories regarding technology adoption and rejection inform AI policies and practices. In offering qualitative case research evidence in combination with quantitative evidence from various global locations, this study offers a four-parted perspective of society’s interaction with AI processes, especially in addressing different essential policy, governance, and ethical issues to control the technologies. Finally, the conclusions underline the need for culture-aware AI deployment and demand advanced global cooperation aimed at the formation of ethical and non-discriminative AI practices across the globe.